2021
DOI: 10.3389/fimmu.2021.650626
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Resolution of Diabetes: C-C Chemokine Motif Ligand 4 Is a Common Target in Different Types of Diabetes by Protecting Pancreatic Islet Cell and Modulating Inflammation

Abstract: Systemic inflammation is related to hyperglycemia in diabetes mellitus (DM). C-C chemokine motif ligand (CCL) 4 is upregulated in type 1 & type 2 DM patients. This study aimed to investigate if CCL4 could be a potential target to improve blood sugar control in different experimental DM models. Streptozotocin-induced diabetic mice, Leprdb/JNarl diabetic mice, and C57BL/6 mice fed a high fat diet were used as the type 1 DM, type 2 DM, and metabolic syndrome model individually. Mice were randomly assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…It seems that anti-inflammation could be an optimal strategy to accelerate wound healing. We previously showed that inhibition of CCL4 by antibodies could decrease the circulating and pancreatic expression of TNF-α and IL-6 in diabetic mice [ 32 ]. Here, we further demonstrated that the genetic knockout of CCL4 could also provide protective effects on diabetic wounds accompanied with downregulated inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that anti-inflammation could be an optimal strategy to accelerate wound healing. We previously showed that inhibition of CCL4 by antibodies could decrease the circulating and pancreatic expression of TNF-α and IL-6 in diabetic mice [ 32 ]. Here, we further demonstrated that the genetic knockout of CCL4 could also provide protective effects on diabetic wounds accompanied with downregulated inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…There are some issues that should be further addressed. Firstly, we have recently shown that the inhibition of CCL4 by the CCL4 antibody could protect pancreatic islets and stabilize glucose metabolism in diabetic mice [ 32 ]. In a diet-induced DM model, CCL4-knockout mice had improved blood sugar levels in the oral glucose tolerance tests as well as lower homeostasis in the model assessment of insulin resistance [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extending these findings further, we found significant change in 7 mRNA (CCL4, IL-18, ARG1, ATM, CD80, CEACAM6, and LAMP3) whose differential expression has been associated with various inflammation-associated chronic disease states. Elevated CCL4 [ 24 ] and IL-18 [ 26 ] result in elevated systemic inflammation and the onset and progression of type 2 diabetes mellitus. In the present study, we observed decreased differential expression of CCL4 and IL-18 at 60 days with prebiotic/probiotic supplementation, which given their associations should be associated with a reduced risk of type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested the critical role of CCL4-related inflammation in the progression of DM. 14 However, the in vivo effects of CCL4 inhibition are complex and the potential mechanisms have not been completely elucidated. The evidence is still lacking regarding the potential effects of CCL4 on gut microbiota, which has been linked to the presence of systemic inflammation and insulin resistance in diet-induced diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, one may speculate the complex effects of direct CCL4 inhibition in vivo. In addition to modulating circulating inflammatory cells and pancreatic inflammation by direct inhibition on CCL4, 14 there might be a novel local mechanism of CCL4 inhibition to modulate gut microbiota particularly family Muribaculaceae/S24-7 and family Atopobiaceae, which then reduce LPS related, toll-like receptor-4 and Nrf2/Keap1-mediated production of inflammatory proteins. While our findings support the hypothesis that direct CCL4 inhibition could modify gut microbiota and related systemic metabolism in diet-induced DM mice, further investigations are required to elucidate the CCL4related signaling pathways in gut.…”
mentioning
confidence: 99%